An educational tool for designing DC motor control systems through FPGA-based experimentation. Issue 1 (January 2015) - Guzmán-Ramírez, E; García, I; Guerrero, E; Pacheco, C
The development of improved power semiconductor devices has allowed different methods of energy conversion to significantly improve their efficiency and be able to operate with higher power levels. These advances have helped to satisfy the growing needs of industrial applications, such as motor drives, power supplies for personal computers, office equipment, spacecraft power systems, laptop computers, and telecommunications equipment. As a result, power electronics is considered a basic subject in engineering careers with a focus on electronics, which leads to an imperative need to count on specialized tools in this area. Furthermore, it is essential to include methodologies to efficiently incorporate these tools into courses. This paper presents an educational web-based tool focused on teaching design of DC motors control systems, with emphasis on design of DC–DC converters and FPGA-based control, under a project-based learning approach. A qualitative research method was utilized in a performed experiment to evaluate this proposed tool.